2022
DOI: 10.1111/famp.12760
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic associations between COVID‐19‐related stress and mental well‐being among parents and children in Hong Kong: An actor–partner interdependence model approach

Abstract: The spread of COVID‐19 and its subsequent social distancing policies have profoundly impacted the lives of parents and children. Prolonged exposure to parenting‐related responsibilities and heightened levels of family conflict under stay‐at‐home orders coupled with reduced access to support systems and resources have rendered parents and children more prone to stress and mental health difficulties. Drawing on a transactional model of parent–child interactions, the present study applied an actor–partner interde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Fifth, because some schools indicated that COVID-19–related items may bring stress to students, we did not include these items in our survey, which made us unable to discuss the potential contribution of the COVID-19 pandemic to mental well-being. The COVID-19 pandemic has been reported to have associations with youth mental well-being . Sixth, owing to the large size of the sample, variables could more easily attain statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, because some schools indicated that COVID-19–related items may bring stress to students, we did not include these items in our survey, which made us unable to discuss the potential contribution of the COVID-19 pandemic to mental well-being. The COVID-19 pandemic has been reported to have associations with youth mental well-being . Sixth, owing to the large size of the sample, variables could more easily attain statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the spread of COVID-19, the Hong Kong government implemented social restrictions such as school closure and “no dine-in” measures (e.g., The Standard, 2022 ). In the face of social restrictions, disrupted child and family routines, reduced work-life balance, reduced family support (e.g., babysitters), scarcity of sanitizing products, unemployment, and financial burden (e.g., Freisthler et al, 2021 ; Yuen et al, 2020 ), local parents were particularly vulnerable to stress, resulting in worse mental health (Chan, 2022 ). Therefore, replication studies are needed to examine the effects of NL-MBP when most parents are no longer experiencing the stress brought by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This challenges the finding that individuals living alone reported feeling lonelier during COVID-19 ( Luchetti et al, 2020 ). Such a finding shows that co-residence during COVID-19 is complex and requires a more nuanced understanding ( Chan, 2022 ).…”
Section: Discussionmentioning
confidence: 99%